2021
DOI: 10.1136/bmjopen-2020-042686
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, safety and response predictors of adjuvant astragalus for diabetic kidney disease (READY): study protocol of an add-on, assessor-blind, parallel, pragmatic randomised controlled trial

Abstract: IntroductionDiabetic kidney disease (DKD) is a prevalent and costly complication of diabetes with limited therapeutic options, being the leading cause of end-stage kidney disease in most developed regions. Recent big data studies showed that add-on Chinese medicine (CM) led to a reduced risk of end-stage kidney disease and mortality among patients with chronic kidney disease (CKD) and diabetes. Astragalus, commonly known as huang-qi, is the most prescribed CM or used dietary herb in China for diabetes and DKD.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Potential adverse effects of the combination of HMs with chemotherapy may appear due to direct toxic effects of HMs, herb-herb, or herb-drug interactions, which are considered major concerns among patients with CRC, especially for those undergoing active chemotherapy (56). However, commonly used HMs such as C. reticulata, A. membranaceus and SJZD are generally perceived as relatively safe treatments with rarely reported adverse effects (57)(58)(59)(60). Studies on animal and clinical trials have shown the safety of these HMs.…”
Section: Discussionmentioning
confidence: 99%
“…Potential adverse effects of the combination of HMs with chemotherapy may appear due to direct toxic effects of HMs, herb-herb, or herb-drug interactions, which are considered major concerns among patients with CRC, especially for those undergoing active chemotherapy (56). However, commonly used HMs such as C. reticulata, A. membranaceus and SJZD are generally perceived as relatively safe treatments with rarely reported adverse effects (57)(58)(59)(60). Studies on animal and clinical trials have shown the safety of these HMs.…”
Section: Discussionmentioning
confidence: 99%
“…More than 60 active ingredients are contained in AS, including AS I-IV, polysaccharides, amino acids and trace elements (Amiri et al, 2020). Chan et al showed that AS reduces macroalbuminuria in patients with type 2 diabetes, stage 2-3 CKD (Chan et al, 2021). Through this RCT, they successfully evaluated the effects of AS and identified related response predictors for more personalized applications and further researches.…”
Section: Astragalus Mongholicus Bunge (Fabaceae)mentioning
confidence: 99%
“…Previous registry studies showed that individualized Chinese medicine (CM) treatment was associated with slower decline of kidney function and reduced risk of end-stage kidney failure and mortality among patients with CKD and diabetes ( Hsieh et al, 2014 ; Lin et al, 2015 ; Huang et al, 2018 ; Chan et al, 2022 ). CM formulations are prescribed based on symptom-based diagnosis ( Chan et al, 2020a ; Chan et al, 2020b ; Chan et al, 2021a ; Chan et al, 2021b ; Chan et al, 2021c ; Shu et al, 2021 ), which predicts renal function decline independent of blood pressure, blood glucose, lipids, and urine albumin control ( Chan et al, 2021b ). The CM used in these cohorts mostly contained a classical CM formulation, namely, Rehmannia-6 complex (R-6, Liu-wei-di-huang-wan) with variations according to the symptom-based diagnosis.…”
Section: Introductionmentioning
confidence: 99%